(untitled) (Al-Academy, 2026)
This research discusses the topic of symbolic interaction theory and its implications in the context of social interaction with industrial products. The research problem is defined as: How does the symbolism of an industrial product affect the user’s interaction with it،shaping interactions and meanings according to symbolic interaction theory? The research aims to reveal how individuals produce social meanings around industrial products through interaction and adaptation to them in daily life. The research examines the topics of symbolic interaction theory and its implications in industrial design،symbolic interaction theory،and the concept of self،the principles of symbolic interaction theory،and symbolic interaction in social contexts،as well as the social interaction between the user and the industrial product in symbolic interaction theory. It was concluded that the social interaction between users and the industrial product depends on language and the communication that occurs between them. Users use symbols that reflect their opinions and feelings toward the product،and these symbols depend on the meanings that arise through the user’s interaction with the product within specific social contexts